Harnessing Fuelwood from Cajanus cajan (L.) Millsp. - Patil, Dhaneshwar B.; Thomas, Moni; Upadhyay, Anubha; Bajpai, A. K.; Bhan, Manish; Bhowmick, A. K. (International Journal of Economic Plants, 2022)
A two-year field trial on lac production on Cajanus cajan (L.) Millsp. was conducted on the research field of Jawaharlal Nehru Krishi Vishwa Vidyalaya, Jabalpur, Madhya Pradesh of India following randomized block design during 2019-20 and 2020-21. After harvest of C. cajan seeds and lac as cash crops, the left-over wood of C. cajan was evaluated for fuelwood (as an energy stove) for the small and marginal farm households. The mean dry weight of total fuelwood (including shoot+root) varied from 1196.67 to 1393.67 g plant-1 in pooled data.The estimated mean weight of total fuelwood (root+shoot) of C. cajan varied from 1447.98 to 1686.34 kg ha-1 in pooled mean of both the years. The value of total (shoot+root) dry fuelwood per plant varied from Rs. 7,239.85 to Rs. 8,431.70 in pooled mean of both the years. This total fuelwood can fulfill daily household requirement of fuelwood upto 3 years (891 to 1037 days) @ 4.06 kg day-1 household-1.